Implementation of Sports Science-Based Strength Training to Improve Coach Competence and the Achievements of the Magetan Regency KONI - Dio Alif Airlangga Daulay; Fifit Yeti Wulandari; Abdul Hafidz; Mochamad Purnomo (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This Community Service (PkM) activity aims to implement strength training based on sport science in order to enhance coaches’ competencies and support the achievement of athletes’ performance at KONI Magetan Regency. The main problem encountered is the limited knowledge of coaches regarding strength training methods aligned with scientific principles, which results in suboptimal athlete performance. The implementation methods of this program include: (1) training and workshops for coaches on the fundamental concepts of sport science in strength training, (2) direct practical assistance using performance measurement instruments, and (3) evaluation of program effectiveness through physical tests and athletes’ performance achievements. This activity is expected to improve coaches’ competencies in designing training programs based on data and evidence, while simultaneously providing tangible impacts on the quality of training and the performance of athletes under KONI Magetan. The targeted outcomes are the development of an applicable strength training model grounded in sport science, the enhancement of coaches’ skills in performance analysis, and the improvement of athletes’ achievements at regional and national levels. Thus, this PkM activity contributes not only to the advancement of coaches’ capacity but also to strengthening the sports performance ecosystem in Magetan Regency.